Central Obesity Plays an Important Role for the Development of Type 2 Diabetes in Bangladeshi Women (Bangladesh Journal of Medical Science, 2014)
Background: Diabetes mellitus coexists at a greater frequency with hypertension, obesity, central obesity, and dyslipidemia. Obesity has been identified as the most important modifiable risk factor in the aetiology of type-2 diabetes mellitus. Central obesity has been shown to be the most pathogenically important in the causation of metabolic disorders including type-2 diabetes. Aims: To determine the association of central obesity with type 2 diabetes in Bangladeshi women. Subjects and Methods: A total of 60 type 2 diabetic female subjects along with 60 healthy female subjects were recruited in this study. Anthropometric indices were measured using standard techniques. Serum glucose was measured using glucose-oxidase method, insulin was measured using ELISA and thyroid hormones were measured using chemiluminescence based automated Immulite Auto analyzer (DPC, USA). Insulin secretory capacity and insulin sensitivity were estimated using fasting glucose and fasting insulin by HOMA-CIGMA software. Results: Waist circumference of the control (89±8) subjects was significantly (p=0.046) lower than the diabetic (94±11) subjects. Waist-hip ratio of the control subjects was significantly lower compared to diabetic subjects. Fasting plasma insulin level in control subjects (7.6±2.2) was significantly (p=0.009) lower compared to diabetic subjects (11.8±9.8). Plasma lipid profile and thyroid hormone status in control and diabetic subjects were not found significantly different. Insulin secretory capacity (HOMA %B) and insulin sensitivity (HOMA%S) in control subjects (93±21, 95±39 respectively) were found to be significantly higher com-pared to diabetic subjects (45±32, 67±42 respectively). In age-adjusted binary logistic regression analysis, waist circumference was found to be significantly associated with diabetes. In multiple linear regression analysis TSH was found to be significantly associated with waist circumference. Conclusion: Waist circumference may be an independent indicator for the development type 2 diabetes in Bangladeshi women which may have influenced by thyroid stimulating hormone (TSH). DOI: http://dx.doi.org/10.3329/bjms.v13i3.19149 Bangladesh Journal of Medical Science Vol.13(3) 2014 p.278-284